2012
DOI: 10.1016/j.inhe.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Location and vocation: why some government doctors stay on in rural Chhattisgarh, India

Abstract: We conducted a qualitative research study in Chhattisgarh State, India, to explore why some qualified medical practitioners decide to stay on in government rural service. The fieldwork consisted of in-depth interviews with 37 practitioners who had an established record of rural service, and data were analyzed using the 'framework' approach for applied policy research. Study participants cited complexes of reasons for staying on, including geographical and ethnic (tribal) affinities, rural upbringing, availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…The monetary benefits, such as pension and gratuity, along with nonmonetary benefits such as less workload, are some of the important factors that attract doctors to join and continue in government service. A recent study on government doctors working in rural areas confirms such findings [45]. Similarly, researchers in a study on rural health-care workers of North Vietnam reported that job stability and income were found to be the major motivating factors [13].…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…The monetary benefits, such as pension and gratuity, along with nonmonetary benefits such as less workload, are some of the important factors that attract doctors to join and continue in government service. A recent study on government doctors working in rural areas confirms such findings [45]. Similarly, researchers in a study on rural health-care workers of North Vietnam reported that job stability and income were found to be the major motivating factors [13].…”
Section: Discussionmentioning
confidence: 71%
“…For some, it may be the challenges in work; for others, it may be the opportunities to use their knowledge and skills; others may find sheer professional and scientific interests rewarding; and for yet others, it may be the ability to influence health outcomes. A recent study in the Indian context suggested that MOs were inspired by unique challenges to influence health outcomes in rural areas [45]. The same study also found that feeling of ‘personal fulfilment’, ‘usefulness of practicing in rural areas’ and ‘professional and scientific interest’ were important factors for work motivation [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations